Molecular signatures underlying neurofibrillary tangle susceptibility in Alzheimer’s disease - Otero-Garcia, Marcos; Mahajani, Sameehan U.; Wakhloo, Debia; Tang, Weijing; Xue, Yue-Qiang; Morabito, Samuel; Pan, Jie; Oberhauser, Jane; Madira, Angela E.; Shakouri, Tamara; Deng, Yongning; Allison, Thomas; et al. (Neuron (Cambridge, Mass.), 2022)
Tau aggregation in neurofibrillary tangles (NFTs) is closely associated with neurodegeneration and cognitive decline in Alzheimer’s disease (AD). However, the molecular signatures that distinguish between aggregation-prone and aggregation-resistant cell states are unknown. We developed methods for the high-throughput isolation and transcriptome profiling of single somas with NFTs from the human AD brain, quantified the susceptibility of 20 neocortical subtypes for NFT formation and death, and identified both shared and cell-type-specific signatures. NFT-bearing neurons shared a marked upregulation of synaptic transmission-related genes, including a core set of 63 genes enriched for synaptic vesicle cycling. Oxidative phosphorylation and mitochondrial dysfunction were highly cell-type dependent. Apoptosis was only modestly enriched, and the susceptibilities of NFT-bearing and NFT-free neurons for death were highly similar. Our analysis suggests that NFTs represent cell-type-specific responses to stress and synaptic dysfunction. We provide a resource for biomarker discovery and the investigation of tau-dependent and tau-independent mechanisms of neurodegeneration. •Method for profiling cells with cytoplasmic protein aggregates from the human brain•Comparison of ∼120K NFT-bearing and NFT-free transcriptomes from AD and controls•Ranked list of 227 synaptic genes associated with NFTs in human prefrontal cortex•Uncoupling of susceptibility to NFT formation and neuronal death Using a new method for profiling single, tangle-bearing neurons from postmortem brain tissue, Otero-Garcia et al. quantify the susceptibility of 20 neocortical subtypes to tangle formation, define signatures of NFT susceptibility, and distinguish molecular changes specifically associated with NFTs from those broadly identified in Alzheimer’s disease.